Lagu Kaulinan Barudak Sebagai Sumber Kreativitas Seni Oleh Oya Yukarya dan Iik Setiawan - Fitragana Riyansabila, - (2020)
ABSTRACT Among the richness of Sundanese traditional arts, the song Kaulinan Barudak or the song Kaulinan urang lembur is a repertoire of traditional Sundanese musical songs that can be a source of creativity ideas. This study aims to describe the interpretation and presentation of Pamones by Oya Yukarya and Sasalimpetan creation by Iik Setiawan in using the Kaulinan Barudak song as a source of creativity ideas. This study uses a descriptive analysis method with a qualitative approach to answer problems in accordance with the problem formulation, namely how the interpretation and presentation of Oya Yukarya and Iik Setiawan in their work. The findings of this study consist of elements of text and context interpretation such as pitch, theme, tempo, processing of arrangements and gending, and presentation of form, function, and public response to works. Pamones by Oya Yukarya is an arrangement of new creations, with a variety of motion processing and new songs of Kaulinan Barudak which go through the interpretation stage so that it is more interesting and unique without reducing its essence. Sasalimpetan creation by Iik Setiawan is a new creation of gending for the song kaulinan sasalimpetan in Rineka Kaulinan Barudak's commercial cassette album 'Mapag Layung', there is a shift in absorption in connection with the need for a particular scene. Keywords: Barudak Kaulinan Song, work creativity, Pamones by Oya Yukarya, Sasalimpetan Creation by Iik Setiawan